Hubungan Response Time Pelayanan Instalasi Gawat Darurat (IGD) Dengan Tingkat Kepuasan Pasien Di Rumah Sakit Islam Surakarta - Shinta Kusumawinahyu, Dhaniar, Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB, Kartinah, A.Kep, S.Kep (2016)
The healthy service in hospital includes the hospitalization and non hospitalization, one of services in hospital is emergency service. The velocity and accuracy are give to emergency patients must be according to competence and service standard, so that caring patients in emergency unit based on response time that fast and right treatment. In principle, everyone wants to get the best service that they chose. Patients satisfaction is one of indicators service quality that given. The purpose of this research is to determine relationship of response time emergency unit service to patient's satisfaction level on red triage and yellow triage. The method used in this research is analytic survey with cross sectional approach. Technique of selecting a sample with accidental sampling, respondents are all patients that come to emergency unit on red triage and yellow triage in conscious and unconscious condition based on family explanation, so can get 88 respondents for each triage, which is red triage and yellow triage. The result using Chi Square test with fisher exact significance level (α=0,05). The result obtained for red triage x²=8,361 with p value 0,015 (p value<0,05), for yellow triage x²=9,131 with p value 0,010 (p value<0,05). Based on the result, the conclusion was there is a relationship of response time emergency unit service to patient's satisfaction on red triage and yellow triage. Recommended that further response time so can achieve patient's satisfaction for the service that they chose.